Role of refined martensite microstructure and intercritical Mn partitioning on austenite reversion in Fe–5Mn-1.5Al-0.2C alloy - Baojia Hu; Hailong Zhu; Shichao Liu; Chengwu Zheng; Liansheng Chen; Dianzhong Li (Journal of Materials Research and Technology)
In this paper, we demonstrate a novel design to accelerate the austenite reversion of a Fe–5Mn-1.5Al-0.2C (wt.%) medium Mn steel (MMS), via a deliberating adding an elevated pre-annealing before conventional intercritical annealing. It is indicated that the kinetics of cementite dissolution and austenite reversion are accelerated simultaneously, and the corresponding heterostructure austenite consisting of a core in low Mn content and a shell in relatively high Mn content is obtained. Meanwhile, the chemical heterogeneity at austenite boundaries significantly improves the thermal stability of reversed austenite during intercritical annealing, as proven by both STEM-EDS measurements and DICTRA simulations. The designed creation of chemical heterogeneity at the austenite boundaries ultimately leads to the appropriate mechanical stability of retained austenite and thus enables sustainable martensite transformation during tensile deformation, enhancing strength and ductility simultaneously.